(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2020)
Leading with sustainability in this high-tech global competition had become a major concern for every single organization all over the world. Here, not only customer expectation but employees’ aspirationswere also accelerating day by day, which had captivated banks too for focusing on the excellency whether it was a company’s product or its company employees. Employee’s high-level performance & development had become an enormous challenge, where it had been acknowledged that manager’s leadership behavior can had a constructive influence on their employees, which stimulate employee’s performance for long term growth. Task performance was most pertinent and directly connected to the organization’s goal, where employees’ behaviors, efforts were rightly indulged into the prescribed job activities, and technical process of organizations. Thus, to retain & increase task performance in banks, there was a need to strategized a perfect leadership style along with other HR tactics. Thus, this analytical study aim was to identify the role of Bank supervisor’s leadership style on their employee task performance, where the hypothesis was tested through a multi-stage sampling of 422 employees from public & private banks in India.